2019
DOI: 10.1038/s41598-019-51542-w
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution and population dynamics of limnic microalgae and their association with physico-chemical parameters of river Noyyal through multivariate statistical analysis

Abstract: The present investigation embarks on understanding the relationship between microalgal species assemblages and their associated physico-chemical parameter dynamics of the catchment region of river Noyyal. Totally, 142 microalgae cultures belonging to 10 different families were isolated from five different sites during four seasons and relative percentage distribution showed that Scenedesmaceae (36.6%) and site S1 (26.4%) with predominant microalgae population. Diversity indices revealed that microalgae communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Our earlier study reported the diversity of microalgae species in catchment region os river Noyyal and their response to the seasonal variation in the physico -chemical characteristics of water (Kumar and Thomas, 2019). We also reported that microalgae were characterized by high H index, lower Simpson dominance value and Margalef index value with indefnite patterns of annual variations.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our earlier study reported the diversity of microalgae species in catchment region os river Noyyal and their response to the seasonal variation in the physico -chemical characteristics of water (Kumar and Thomas, 2019). We also reported that microalgae were characterized by high H index, lower Simpson dominance value and Margalef index value with indefnite patterns of annual variations.…”
Section: Discussionmentioning
confidence: 85%
“…Our earlier study reported the population dynamics and diversity indicies of 142 fresh water microalgae species of river Noyyal and their response to the seasonal variation with physico -chemical charactersicts of water (Kumar and Thomas 2019). The study also provided the checklist of microalgae in abundance, the distribution and community structure in the ve collection sites from catchment region of river Noyyal.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria frequently accounted for over 80% of the total phytoplankton. Several potentially toxic genera, such as Microcystis, Cylindrospermopsis, Planktotrix, Planktolyngbya, and Anabaena, were dominant throughout our study period (Barros et The ecology of phytoplankton in aquatic environments is affected by seasonal changes, leading to uctuations in species diversity, evenness, the Shannon-Wiener index, and cell density (Sun et al 2023;SureshKumar et al 2019). Temperature is a signi cant factor that regulates the growth of phytoplankton (Somdee et al 2013;Wang et al 2023).…”
Section: Discussionmentioning
confidence: 97%
“…Reactive silicate is still higher in seawaters and not a major factor determining the growth of the local diatom blooms. 29…”
Section: Of Total Microalgae Count With Physicochemical Propertiesmentioning
confidence: 99%